Electrochemical intramolecular C–H/N–H functionalization for the synthesis of isoxazolidine-fused isoquinolin-1(2H)-ones. Issue 1 (3rd December 2019) - Zhang, Lin-Bao; Geng, Rui-Sen; Wang, Zi-Chen; Ren, Guang-Yi; Wen, Li-Rong; Li, Ming
Abstract : A general and practical protocol for the construction of isoxazolidine-fused isoquinolin-1(2 H )-ones has been described by electrochemical-oxidation-induced intramolecular annulation via amidyl radicals. Abstract : A general and practical protocol for the construction of isoxazolidine-fused isoquinolin-1(2 H )-ones has been described by electrochemical-oxidation-induced intramolecular annulation via amidyl radicals. In an undivided cell, isoquinolinones could be easily generated from various available amides bearing CONHOR groups under metal-free, additive-free and external oxidant-free conditions. Moreover, this transformation proceeded smoothly by using cheap 95% ethanol as the green solvent and could be extended to the gram scale.